Hybrid multi criteria decision methods for optimal cloud selection in mobile cloud computing - Sindhu Kurup; Hassan Sadashiva Guruprasad (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Cloud computing provides the users with flexibility of using computational systems on demand at nominal cost. Execution of resource intensive task on mobile devices is still a big challenge due to resource constraints of mobile devices. Utilizing the servi ces of resource rich cloud servers for offloading the task from mobile device can overcome the resource constraint issues of mobile devices. When offloading the task, there is a need to choose an optimal cloud server from a pool of available cloud servers offering similar services. The proposed work uses three hybrid multicriteria decision methods for choosing the optimal cloud server and comparative analysis of the three methods are presented. Real time cloud servers located at four different regions are c onsidered with six quality of service ( QoS) attributes. The results indicate that all the three methods are viable solutions in selecting the optimal cloud server with multi - objective optimization on the basis of ratio anal ysis (MOORA) providing a faster response compared to other two methods. Sensitivity analysis performed proves the correctness and effectiveness of the proposed methodology.